HYPNOTEACHING IN ISLAMIC RELIGIOUS EDUCATION : ENHANCING STUDENT LEARNING MOTIVATION - Fiqra Muhamad Nazib; Yufi Mohammad Nasrullah; Madya Mohd Noor bin Mohd; Masripah Masripah; Farah Hanifah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study explores the application of hypnoteaching in Islamic Religious Education (PAI) learning management to enhance senior high school students’ motivation. Using a qualitative descriptive approach through observations, interviews, and documentation at SMAN 14 Garut, the findings reveal that hypnoteaching-based planning, implementation, and evaluation improve students’ focus, participation, and learning enthusiasm. Integrating psychological and pedagogical perspectives, this study positions hypnoteaching as a holistic and applicable approach within Islamic education. The results highlight its potential to be adopted more broadly in PAI learning contexts, offering practical guidance for teachers in designing motivating and student centered instruction.